Identifying nitrogen sources to thermal tide pools in Kapoho, Hawai'i, U.S.A, using a multi-stable isotope approach. Issue 1 (15th February 2016) - Wiegner, Tracy N.; Mokiao-Lee, Ambyr U.; Johnson, Erik E.
Abstract: Nitrogen (N) enrichment often results in coastal eutrophication, even in remote areas like Hawai'i. Therefore, determining N sources to coastal waters is important for their management. This study identified N sources to tide pools in Kapoho, Hawai'i, and determined their relative importance using three stable isotopes (δ 15 N, δ 18 O, δ 11 B). Surface waters and macroalgal tissues were collected along 100-m onshore-offshore transects in areas of high groundwater input for three months at low tide. Water samples from possible N sources were also collected. Mixing model output, along with macroalgal δ 15 N values, indicated that agriculture soil (34%) was the largest anthropogenic N source followed by sewage (27%). These findings suggest that more effective fertilizer application techniques and upgrading sewage treatment systems can minimize N leaching into groundwater. Overall, our multi-stable isotope approach for identifying N sources was successful and may be useful in other coastal waters. Highlights: Multi-stable isotope approach successfully identified N sources to tide pools. NO3-isotopes identified agriculture and groundwater as key N sources, not sewage. δ 15 N indicated tide pool algae used N from agricultural soils. Mixing model apportioned contributions of N sources to tide pools. Agricultural soils were largest anthropogenic N source to tide pools.